2017
DOI: 10.1016/j.ajog.2017.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes in fetuses with cardiac anomalies and the impact of delivery route

Abstract: BACKGROUND Congenital fetal cardiac anomalies compromise the most common group of fetal structural anomalies. Several previous reports analyzed all types of fetal cardiac anomalies together without individualized neonatal morbidity outcomes based on cardiac defect. Mode of delivery in cases of fetal cardiac anomalies varies greatly as optimal mode of delivery in these complex cases is unknown. OBJECTIVE We sought to determine rates of neonatal outcomes for fetal cardiac anomalies and examine the role of atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 21 publications
2
20
0
4
Order By: Relevance
“…3 Tanının prenatal dönemde konması değerlendirme açısından optimizasyonu sağlamış olsa da, ideal doğum şeklinin sezaryen veya vajinal doğum olması konusunda kesin sonuçlar bulunmamaktadır. 16,17 Tablo 5. Subgrup analizlerine göre doğum ağırlığı, APGAR skorları, gebelik haftaları ve maternal yaşın karşılaştırması.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…3 Tanının prenatal dönemde konması değerlendirme açısından optimizasyonu sağlamış olsa da, ideal doğum şeklinin sezaryen veya vajinal doğum olması konusunda kesin sonuçlar bulunmamaktadır. 16,17 Tablo 5. Subgrup analizlerine göre doğum ağırlığı, APGAR skorları, gebelik haftaları ve maternal yaşın karşılaştırması.…”
Section: Discussionunclassified
“…[20][21][22][23] Yapılan başka bir çalışmada ise, prenatal kardiyak anomaly tanısı almış hastalarda, planlanmış sezaryen ve vajinal doğum karşılaştırılmış, sezaryen doğumun kötü neonatal sonuçlarda azalmayla ilişkili olmadığı gösterilmiştir. 17 Prenatal kardiyak anomaly tanısı alan yenidoğanların değerlendirildiği bir çalışmada, bu yenidoğanların, sıklıkla planlı sezaryen nedeni ile postnatal tanı alanlara göre daha erken doğdukları saptanmıştır. 24 Trento ve ark.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In the EPICARD study, Laas et al found that overall preterm newborns with CHD, particularly those who were born at <35 weeks of gestational age, had a substantially higher risk of mortality than those born at term (37-41 weeks), but the same group showed that the higher risk of preterm birth in newborns with CHD, was essentially due to spontaneous labor and not scheduled delivery (35,36). The attempted route of delivery (vaginal or caesarian section) for fetal cardiac anomaly had no impact on neonatal morbidity while prenatal diagnosis reduced the need for invasive respiratory support (37).…”
Section: Impact Of Prenatal Diagnosis Of Chd On Morbiditymentioning
confidence: 97%
“…Не рекомендуется принимать решение о преждевременном стимулировании родовой деятельности, если речь не идет о жизненных показаниях по состоянию матери или плода. К настоящему времени необходимость или потенциальные преимущества операции кесарева сечения у женщин при выявлении порока сердца у плода убедительно не доказаны (за исключением врожденных пороков сердца с внутриутробной декомпенсацией кровообращения для повышения шанса на выживание) [8]. Тем не менее данные опубликованных исследований позволяют утверждать, что решение о родоразрешении через естественные родовые пути в большинстве случаев принимается в отсутствие информации о наличии врожденного порока сердца у плода.…”
unclassified